Longitudinal Frequencies of Blood Leukocyte Subpopulations Differ between NOD and NOR Mice but Do Not Predict Diabetes in NOD Mice. (4th February 2016) - Telieps, Tanja; Köhler, Meike; Treise, Irina; Foertsch, Katharina; Adler, Thure; Busch, Dirk H.; Hrabě de Angelis, Martin; Verschoor, Admar; Adler, Kerstin; Bonifacio, Ezio; Ziegler, Anette-Gabriele
Abstract : Immune phenotyping provides insight into disease pathogenesis and prognostic markers. Trajectories from age of 4 to 36 weeks were modeled for insulin autoantibodies and for leukocyte subpopulations in peripheral blood from female NOD (n = 58 ) and NOR (n = 22 ) mice. NOD mice had higher trajectories of insulin autoantibodies, CD4 + and CD8 + T lymphocytes, B lymphocytes, IgD + IgM − B lymphocytes, and NK cells and lower trajectories of CD4 + CD25 + T lymphocytes, IgM + B lymphocytes, granulocytes, and monocytes than NOR mice (allp < 0.001 ). Of these, only the increased IAA trajectory was observed in NOD mice that developed diabetes as compared to NOD mice that remained diabetes-free. Therefore, the profound differences in peripheral blood leukocyte proportions observed between the diabetes-prone NOD mice and the diabetes-resistant mice do not explain the variation in diabetes development within NOD mice and do not provide markers for diabetes prediction in this model.